Formalisasi Syari’at Islam di Indonesia: Pendekatan Pluralisme Politik dalam Kebijakan Publik - M. Zainal Anwar (Millah: Journal of Religious Studies, 2011)
This paper discusses about the formalization of Islamic shari’a in public policy area in Indonesia. The writer will use a pluralism of political perspective to discuss this paper. In pluralism of political approach in public policy, there several questions will guide a writer in this study. The important questions in pluralism of political approach are; who engaged in the process of decision-making; who’s choice that accepted as a decision; and who can put up influence to the outcomes. After we discuss wide range a concept of pluralism of politics and public policy, this paper will study a discourse and the aspiration of Islamic shari’a; formalization from district level until central level and the minorities’ response toward public policy that oriented to special religion. This paper, systematically, will begin from the perspective of pluralism of politics to examine many problems that discussed and will be finished with the conclusion.